The Analysis of Partnership Patterns and Broiler Supply Chain Management - Purnomo, Sulistyo Sidik (Current Topics in Agricultural Sciences Vol. 2, 2021)
The livestock sector, especially poultry has a great opportunity to be developed. For this reason, a vertical integration system is needed as a business from upstream to downstream. To understand this, the research is carried out on partnership patterns and supply chain management as an effort to fulfill access and production of broilers. The aim of research was to know the cooperation of broiler farming partnerships and productivity in terms of financial aspects. To achieve this goal, an analysis was carried out: the potential for partnerships with PIR broiler patterns, the feasibility of broiler business through PIR and independent partnerships, and benchmarks for plasma business performance in partnerships. The results of analysis showed that most of the live broiler chickens (90%) were sold to collectors. Then by the traders it was distributed to various customers: traditional markets, modern markets, restaurants, hotels, catering and end to consumers. The results of analysis of partnership cooperation, the coefficient of flexibility was 1.41, the dependence of partners was 0.26, 2.32 and 0.033. With the success rate of broiler farming partnerships, the following coefficients were obtained: net profit 0.26, the time period for receiving business results is 0.35, 3.14, and 0.06 while productivity growth was 1.40, 16.09 and 1.00. Thus, viewed from the financial aspect, the partnership business pattern is more profitable than the independent business pattern. The partnership system can run well depending on the commitment of the two partners who are partners, in this case the core company and plasma farmers.